RETRACTED Isolation, characterization and expression of a gene from Brassica napus encoding a LIM-domain protein - Huang, C Z (Plant physiology and biochemistry : PPB, 2006)
This article has been retracted consistent with Elsevier Policy on Article Withdrawal. Please see http://www.elsevier.com/locate/withdrawalpolicy The Publisher apologizes for any inconvenience this may cause